The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2214/ajr.17.18554
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes Tumor of the Breast: Ultrasound-Pathology Correlation

Abstract: There is substantial overlap in the sonographic features of benign and borderline or malignant phyllodes tumors. Understanding the clinical and sonographic features of phyllodes tumors may aid the radiologist in predicting biological behavior, including the likelihood of benign versus borderline or malignant phyllodes tumors at pathologic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Jalaguier-Coudray et al and Wiratkapun et al in their papers reported that in ultrasound, present of internal cystic spaces or round cysts in lesions that appear like fibroadenoma is highly suggestive of phyllodes tumors. [ 36 , 37 ] A previous study has also reported a high percentage of cystic components in malignant PTs (80%), albeit a small sample size. [ 38 ] In contrast, equal presence of cystic component in all categorization, was seen in another study.…”
Section: Discussionmentioning
confidence: 97%
“…Jalaguier-Coudray et al and Wiratkapun et al in their papers reported that in ultrasound, present of internal cystic spaces or round cysts in lesions that appear like fibroadenoma is highly suggestive of phyllodes tumors. [ 36 , 37 ] A previous study has also reported a high percentage of cystic components in malignant PTs (80%), albeit a small sample size. [ 38 ] In contrast, equal presence of cystic component in all categorization, was seen in another study.…”
Section: Discussionmentioning
confidence: 97%
“…According to Liberman et al most of phyllodes tumors exhibited hypoechoic internal echotexture and posterior acoustic enhancement and the presence of cystic spaces on USG was known to be more common in malignant cases (6). According to Kalambo et al an irregular shape, noncircumscribed margins, and/or mass size > 7 cm may indicate more borderline and malignant subtypes of phyllodes tumors (7). In our case, the mass was observed as a mainly hyperechoic mass, with oval shape, indistinct margin, and cystic portions.…”
Section: Discussionmentioning
confidence: 99%
“…On ultrasonography (USG), most of these tumors exhibited lobulated contours, smooth margins, hypoechoic echotexture, with posterior acoustic enhancement. Malignancy may be suspected if the tumor contains cystic space, or if it is with an irregular shape or non-circumscribed margin (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Although juvenile fibroadenoma is easily distinguishable from PT from a histological point of view, the condition can initially cause signs and symptoms that are similar to those of PT. Moreover, the US features are quite similar [ 17 ] and do not permit either the differentiation of PT from juvenile fibroadenoma or the evaluation of the type of PT [ 18 ]. Only magnetic resonance imaging (MRI) can be useful for the diagnosis and to establish the relationship of the mass with the surrounding normal tissue [ 19 ].…”
Section: Discussionmentioning
confidence: 99%